2013
DOI: 10.1002/dc.23019
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lesion of undetermined significance in thyroid FNA revisited

Abstract: Controversy exists regarding the validity of follicular lesion of undetermined significance (FLUS), an indeterminate diagnostic category of The Bethesda System for Reporting Thyroid Cytopathology (BSRTC). According to BSRTC, FLUS carries a 5-15% risk of cancer. This study was designed to determine if cytomorphology could stratify FLUS into subgroups with different risks of malignancy. Reports of 127 consecutive FNAs reported as FLUS with subsequent tissue diagnoses were evaluated for the presence of various cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The Bethesda System for Reporting Thyroid Cytopathology (BSRTC) has six categories, one of which is AUS or FLUS, which is a heterogeneous group that is difficult to classify as benign, follicular neoplasm, suspicious for malignancy, or malignant. [1][2][3][4][5][6] In AUS/FLUS, the risk of malignancy in resected nodules is 5 to 15%, but a variation from 6 to 48% is in record. [6][7][8][9] It has been reported that with repeated FNAB in AUS/ FLUS cases, about 56 to 68% will have a more definitive result and 15.6 to 48.6% will be interpreted as AUS/FLUS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bethesda System for Reporting Thyroid Cytopathology (BSRTC) has six categories, one of which is AUS or FLUS, which is a heterogeneous group that is difficult to classify as benign, follicular neoplasm, suspicious for malignancy, or malignant. [1][2][3][4][5][6] In AUS/FLUS, the risk of malignancy in resected nodules is 5 to 15%, but a variation from 6 to 48% is in record. [6][7][8][9] It has been reported that with repeated FNAB in AUS/ FLUS cases, about 56 to 68% will have a more definitive result and 15.6 to 48.6% will be interpreted as AUS/FLUS.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although it has been suggested that the usage of AUS/FLUS should not exceed 7% of thyroid FNABs, 3,7,9,10 there is variation of this percentage from 3 to 29% across laboratories and from 2.5 to 28.6% among cytopathologists. 5 Ultrasound findings can facilitate reaching a diagnosis of nodules with AUS/FLUS, 11 although they may not differentiate benign from malignant nodules. 7 As stated earlier, the aim of this study was to define any correlation between different clinical and US features with the final histopathology in patients with a diagnosis of AUS/FLUS, and if these data can be used in planning the surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by them show that cases assigned to the AUS/AFLUS category can ultimately be assigned to other Bethesda System groups. 39 Jing et al 26 conducted a study in which they reassessed 40 conducted a study, on the basis of which they wanted to determine whether the AUS/AFLUS category should be divided into further subcategories according to the malignancy rate. Studies suggest that cases of AUS/AFLUS showing the presence of focal nuclear atypia carry a higher risk of cancer than other cases assigned to AUS/AFLUS and fit better into the category of SM, while those cases that do not show atypical nuclear characteristics show the risk of malignancy recommended for TB-SRTC AUS/AFLUS categories.…”
mentioning
confidence: 99%
“…Studies suggest that cases of AUS/AFLUS showing the presence of focal nuclear atypia carry a higher risk of cancer than other cases assigned to AUS/AFLUS and fit better into the category of SM, while those cases that do not show atypical nuclear characteristics show the risk of malignancy recommended for TB-SRTC AUS/AFLUS categories. 40 Generally, compared to previous systems, TBSRTC results in reducing the number of non-diagnostic/indeterminate cases and enables better clinical usefulness of the results of a FNA of the thyroid gland. This is probably due to the introduction of more standard criteria for interpreting and reporting.…”
mentioning
confidence: 99%
“…Problems of inadequacy was exceeded by this study method, pathologists evaluated cyto-morphologic and histomorphologic findings of TP slides in every stage of aspiration [21]. It is well understood how important it is to obtain benign and malignant lesions with this method.…”
Section: Discussionmentioning
confidence: 99%